IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI DESA DI KABUPATEN KEBUMEN (KAJIAN PERATURAN BUPATI KEBUMEN NOMOR 48 TAHUN 2015 TENTANG SISTEM INFORMASI DESA DI KABUPATEN KEBUMEN) - Rizki Dwi Nur Sidiq; Sri Suwitri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The implementation of village information system policy in Kebumen Regency is an effort of regency government that aims to realize easiness of village data processing and improvement of public information disclosure at village government level. However, there are still many villages that are still not optimal in implementing such policies, especially in applying the village information system offline and online.This study aims to describe and analyze the implementation of the village information system policy in Kebumen District and to identify and analyze the factors that influence the implementation of village information system policy in Kebumen District.The researcher uses an implementation model that the researchers arrange with top-down approach based on George Edward III, van Meter and van Horn and Merile S. Grindle theory. Factors that researchers use in discussing the implementation of the policy under study are the standards and objectives of policy, communication, resources, and attitudes of the implementers.It is found that the implementation of the village information system policy in Kebumen Regencywas not optimal due to the influence of factors lack of provisions that encourage the implementer to meet the standards and objectives such as reward and punishment systems make compliance with standards and goals less attention, lack of financial resources, human resources and facilities lack of intensity of communication carried out by implementers. The researchers suggest to hold a SID management competition to increase motivation in meeting standards and objectives, increasing the number of training and SID operators, and the use of village funds to develop internet infrastructure at the village level.